The Way EFL students' using English language in oral communication in the classroom (what they concern) - Siagian, Siti Hajar; -, Wulan Novita Sari (Indonesian Journal of ELT and Applied Linguistics, 2024)
Oral communication skills in English are one of the important aspects that must be mastered by EFL (English as a Foreign Language) students to support real language learning and application. However, the use of English in oral communication in the classroom is often a challenge for students, especially in environments where English is not their mother tongue. This research aims to identify and analyze the way EFL (English as a Foreign Language) students use English in oral communication in the classroom and what they concern about. Through qualitative methods and data collection in the form of class observations and interviews, the subject of this research is an English education student. The research results show that the students’ focus is: grammar, pronunciation, and listening. This research provides important insights for educators in designing teaching strategies that support students’ oral communication skills in EFL learning environments. By creating a learning environment that supports and encourages students to actively speak English, it is hoped that their oral communication skills can develop significantly.